The existence of implicit pedagogical theories among the Information Culture Program (ICP) instructors at the Sistema de Bibliotecas of the Universidad de Antioquia - Llano Ochoa, Francisco Javier; Yarza de los Ríos, Víctor Alexander (Revista General de Información y Documentación, 2017)
The present article sets out to explore the existence of implicit pedagogical theories among the Information Culture Program (ICP) instructors at the Sistema de Bibliotecas of the Universidad de Antioquia. Using a case-study approach, the pedagogical practices at the library are analyzed. Moreover, the Narrative-Conceptual Pedagogical Framework (NCPF) serves as a theoretical vantage for the conceptualization of the data. The results show that both instructional and knowledge transmission practices at the Central Library are not pedagogically-driven. This points to a need to consolidate a pedagogical mindset among instructors through the creation of suitable spaces for reflection capable of laying out the foundations of an informational culture.
Keywords: Implicit theories; education; pedagogy; educational practice; University Library